HUBUNGAN TINGKAT HARGA DIRI (SELF-ESTEEM) DENGAN TINGKAT ANSIETAS ORANG TUA DALAM MERAWAT ANAK TUNAGRAHITA DI SDLB C NEGERI DENPASAR - Lisnayanti, Wayan (Coping: Community of Publishing in Nursing; Vol 3 No 2 (2015): JURNAL EDISI MEI-AGUSTUS 2015, 2015)
The existence of mental retardation children in a family may cause anxiety on each member of the family especially the caregiver or parents. Anxiety level parents who have mental retardation children can be affected by several factors including self-esteem. This research was conducted to look at the relationship between the self-esteem and anxiety level. Type of this research is a descriptive, correlation design with a cross-sectional study. This research uses 81 parents of mild mental retardation children at SDLB Negeri C Denpasar as a sample that used a purposive sampling technique. Data collection was carried out in may 2014 using the questionnaire answered by the respondent. The results of this research suggests as many as 52 respondent (64,2%) with moderate self-esteem, 21 respondent (25.9%) with high self esteem and 8 respondent (9.9%) with low self esteem. Whereas, for anxiety levels, there are 34 respondent (42,0%) with mild anxiety, 30 respondent (37.0%) with moderate anxiety, 10 respondent with severe anxiety (12.3%) and 7 respondent (8.6%) without anxiety. Based on statistical tests using Rank Spearman with ? = 0.05, discovered the value of p = 0.00 (p<?) and r = - 0,656 means relationship between self-esteem and parents anxiety level in the care of mental retardation children in SDLB Negeri C Denpasar that are strong and have a negative relationship, the higher self esteem then the lower level of anxiety. Based on the results of this study, researchers hope the school and the health services can work together and make use of the results of this research in provide counseling or health education to parents of mentaly retardation children that can reduce the level of anxiety which was owned during the care of mental retardation.
Keywords: Self-esteem, anxiety, mental retardation